Pengaruh Pemberian Jus Jambu Biji Merah (Psidiumguajava L.) Terhadap Jumlah Sel Eritrosit, Hemoglobin, Trombosit dan Hematokrit pada Mencit Putih - Arifin, Helmi; Agustina, Agustina; Rizal, Zet (Jurnal Sains dan Teknologi Farmasi, 2013)
Evaluation of the effect of red guava juice (Psidiumguajava, L.) on hematology parameters (red blood cell, hemoglobin, thrombocyts, and hematocrit) to female white mice has been done. The juice was administered orally with variation of doses at 25, 50 and 100 % one times a day for 7, 14, and 21 days respectively. As a control group was female white mice administered aquadest.  Results showed that administration of guava juice with a variation of dose did not influence red blood cell counts, hemoglobin and hematocrit, but increased thrombocytes  levels.